Le volatili rappresentazioni di piazza Martim Moniz a LIsbona - Tulumello, Simone (2014)
The role of information has assumed, in the last decades, a central place in planning theory and research, especially around the capacity of misinformation to shape power relationships in the political arenas. The theme of counter-information, with its capacity to contrast the institutionalized information, has contextually emerged in the public debate. The authors suggest a parallel to the duality of misinformation/counter-information, building on the representation of urban spaces and processes: “mis-representation“ versus “counter-representation”. A Reading of the flux of representations on Martim Moniz Square in Lisbon is given and the swift transformations of this place are highlighted. Therefore, the relationship between institutional policies and local practices, between spaces for conflict/dialogue, and their representations are debated as crucial for the capacity (or not) of grass-root rquests to soar at the role of organized action.